Peran Modal Manusia dan Kecerdasan Sosial serta Kepemimpinan terhadap Kinerja Inovasi - Meliza Prawita; Kusuma Chandra Kirana; Didik Subiyanto (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This research that I research focuses on knowing the influence of the role of human capital and social intelligence and leadership on innovation performance. The aim is to evaluate that a role for human capital, social intelligence and leadership is needed in the company. The population used in this study also came from the Sumber Mataram Makmur Company which is located in the city of Yogyakarta. This research is quantitative, with the method used is non-probability sampling. The data analysis technique used is the classical assumption test, multiple linear regression test and the research hypothesis test. So as to obtain research results that prove that the role of human capital has a positive effect on innovation performance, social intelligence variables have a positive and significant influence on innovation performance, and leadership has no effect on innovation performance, and the role variables of human capital, social intelligence, and leadership have a positive effect on innovation performance. simultaneous influence on innovation performance. Keywords: The role of human capital, social intelligence, leadership, innovation performance